Narrativas de sobreviventes ao cárcere e suas aprendizagens biográficas - Correia, Fernanda Bispo (2023)
This text presents reflections on the biographical learning trajectories of two women and a trans man who survived the situation of incarceration in the Female Prison of Nossa Senhora do Socorro-SE (PREFEM). From the perspective of the biographical approach, it seeks to discuss/reflect on memories, experiences, memories of incarceration/deprivation of liberty processes. Thus, during the research process, narratives emerged about social, affective, punitive, pedagogical practices, as well as experiences after this experience, in a post-prison world. It is among the objectives to analyze which and how the biographical learning (formal, non-formal or informal) - according to studies developed by Alheit and Dausien (2006, 2007, 2010) and Alheit (2011), - experienced in prison by these people who survived the prison, were assimilated and echoed in life outside the grilles, after reentry into society. It is necessary to point out that the temporal structure of the learning process in individual biographies refers to the fundamental question of how training is not reduced only to its organized and institutionalized forms. Thus, it contemplates the entire complex of daily experiences, episodes of transition and crisis, and these aspects are highlighted in the analyses. In its lived dimension, learning is also linked to the context of a concrete biography. On the other hand, it is also the condition or mediating instrument in which biographical constructions, as reflexive forms of experience, can develop and transform. It was also one of the purposes to carry out a sensitive listening, always seeking to guarantee respect for the shared narratives. Thus, we worked from a comprehensive-interpretative approach, because, according to this perspective, it is strongly emphasized, as Minayo (2010) defends, the basic recognition that in the act of researching the interpretive and cognitive processes inherent to life society need to be taken into account. Thus, I take the biographical narrative as a method and rely on authors such as Souza (2007, 2014), Bondía (2002), Delory-Momberger (2011, 2014), as these researchers think about how these experiences, manifested in their narratives, translate into biographicality (Alheit, 2007). For considerations about gender and the place of women in history, and also of a trans man, concepts dear to my research, I bring up authors such as Scott (1992, 2005), Gonçalves (2006), De Los Rios (2005), Angotti (2018), Alves (2001), Preciado (2014, 2019). This study proposes, therefore, to contribute to the social visibility of themes that refer to the life trajectory, practices and challenges of people who have survived prison.